Developing a minifesta for effective academic-activist collaboration in the context of the climate emergency - McLaren, Duncan P.; Anderson, Christine; Barry, John; Castán Broto, Vanesa; de Cheveigné, Suzanne; Chilvers, Jason; Crowther, Alison; Hupé, Jean-Michel; Kalaugher, Liz; Labussiere, Olivier; Rothery, Tina L.; Nadai, Alain; et al. (Frontiers in Education, 2024)
Justice-oriented climate activism is proliferating. Many scholars aspire to deliver research that supports activism. However, measures of impact for research evaluation and funding purposes place little weight on the use of research by activists. Here we consider how academics and academia might effectively support and enable climate activism. We report outcomes from a series of online deliberative workshops involving both activists and academics from several European countries. The workshops were carefully facilitated to create space for discussion, sharing of experiences and the development of proposals for the future. The outcomes take the form of a set of principles (a 'minifesta') for academic-activist engagement generated by the group. In discussing the process and outputs, we argue that a focus on inclusion can help support politically transformative change of the scale and urgency required. We suggest that this also demands a shift in attitudes towards the role of activism and activists in collaborative processes. We further discuss the inevitable incompleteness of this process, arguing that incompleteness is, itself, a feature of inclusive engagement. We conclude that scholars working on climate issues in any discipline could benefit from increasing mutually supportive collaboration with activists; and that such collaboration and inclusion could help liberate democracy from authoritarian tendencies and market influences. Collaborative engagements generate legitimate, rich, and impactful outcomes even with the limitations posed by COVID19. We, therefore, commend both the model of engagement and the principles it generated for our colleagues and peers.